The contribution of incentive tax measures to increase the collection of tax debts –Case study of the Tax Directorate of wilaya of M'sila for the period 2017-2021 - ouis, aridj; mokhtari, boulenoir (Journal of Research in Finance and Accounting, 2023)
This paper aimed to highlight the most important incentive measures developed by the tax legislator to collect the accumulated tax debts of individuals and institutions, especially in light of the conditions related to Covid-19, through an analytical study at the level of the Tax Direction the Wilaya of M’sila for the period [2017-2021]. The study concluded that the contribution of these procedures differed from one procedure to another, but the conditional reduction was one of the best procedures, as the tax debt collection rate reached more than 80% during the study period, and this is due primarily to the specificity of this procedure in resolving tax disputes and its comprehensiveness of all taxes and fees.